The Response of Photosynthetic Functions of F1 Cutting Seedlings From Physocarpus amurensis Maxim (♀) × Physocarpus opulifolius “Diabolo” (♂) and the Parental Seedlings to Salt Stress - Nan, Xu; Huihui, Zhang; Haixiu, Zhong; Yining, Wu; Jinbo, Li; Li, Xin; Zepeng, Yin; Wenxu, Zhu; Yi, Qu; Guangyu, Sun (Frontiers in Plant Science, 2018)
This paper selected clonal cutting seedlings from the F1 hybrid varieties of Physocarpus amurensis Maxim (♀) × Physocarpus opulifolius “Diabolo” (♂) as research material to study the response of the photosynthetic gas exchange parameters and chlorophyll fluorescence parameters of Physocarpus amurensis hybrids and their parental leaves to NaCl stress (with concentrations of 0, 50, 100 and 200 mmol•L-1). The results showed that under saline stress, the stomatal conductance (Gs), transpiration rate (Tr), and net photosynthetic rate (Pn) of the three kinds of P. amurensis all significantly decreased. When the NaCl concentration was below 100 mmol•L-1, the intercellular CO2 concentration (Ci) of leaves of the three samples declined with the increase of salt concentration; however, when the concentration increased to 200 mmol•L-1, Ci did not decrease significantly, especially when the Ci of P. opulifolius “Diabolo” presented a slight increase. This indicated that the decline of photosynthetic carbon assimilation capacity induced by saline stress was the consequence of interaction between stomatal factors and non-stomatal factors, and the non-stomatal factors played an important role when the saline concentration was below 200 mmol•L-1. Compared with P. amurensis, the photosynthetic gas exchange capability of P. opulifolius “Diabolo” leaves was more sensitive to saline stress, and the limitation of non-stomatal factors was relatively evident, but the photosynthetic capacity of hybrid Physocarpus amurensis Maxim leaves with the desired purple color was improved compared with Physocarpus amurensis. Under saline stress, the PSII activity of the three kinds of P. amurensis leaves declined, the electron transfer was inhibited, and obvious signs of photoinhibition were present. The PSII activity of P. opulifolius “Diabolo” leaves was more sensitive to saline stress than in Physocarpus amurensis. Under saline stress, the NPQ of P. opulifolius “Diabolo” leaves decreased greatly, while under high saline concentrations the degree of photoinhibition in Physocarpus amurensis and hybrid P. amurensis were reduced due to a relatively high NPQ. With the increase of saline concentration, the Vk of P. amurensis and hybrid P. amurensis leaves presented a decreasing trend, but the Vk of P. opulifolius “Diabolo” leaves increased slightly.